2008
DOI: 10.1785/0120060411
|View full text |Cite
|
Sign up to set email alerts
|

Late Holocene Rupture of the Northern San Andreas Fault and Possible Stress Linkage to the Cascadia Subduction Zone

Abstract: We relate the late Holocene northern San Andreas fault (NSAF) paleoseismic history developed using marine sediment cores along the northern California continental margin to a similar dataset of cores collected along the Cascadia margin, including channels from Barclay Canyon off Vancouver Island to just north of Monterey Bay. Stratigraphic correlation and evidence of synchronous triggering imply earthquake origin, and both temporal records are compatible with onshore paleoseismic data. In order to make compari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
148
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(149 citation statements)
references
References 110 publications
(149 reference statements)
1
148
0
1
Order By: Relevance
“…The shear stress perturbation along the CSZ is larger than along the SAF, mostly because the sense of shear on the CSZ is thrust motion as opposed to strike slip, and tends to inhibit failure along the coastline. A smaller coefficient of friction in this region, m f = 0.4 [Goldfinger et al, 2008], makes the Coulomb stress perturbation at 10 km depth near the shoreline about −0.4 MPa inhibiting failure, smaller than at either the SAF or Alpine fault and corresponding to a stress perturbation rate of −0.04 kPa/yr, much smaller than the tectonic loading rate. Because the fault zone straddles the coastline, the relative strengthening and weakening of different sections of the fault could possibly lead to a shift in the type of rupture on the CSZ.…”
Section: Eustatic Ocean Loading At the Cascadia Subduction Systemmentioning
confidence: 85%
“…The shear stress perturbation along the CSZ is larger than along the SAF, mostly because the sense of shear on the CSZ is thrust motion as opposed to strike slip, and tends to inhibit failure along the coastline. A smaller coefficient of friction in this region, m f = 0.4 [Goldfinger et al, 2008], makes the Coulomb stress perturbation at 10 km depth near the shoreline about −0.4 MPa inhibiting failure, smaller than at either the SAF or Alpine fault and corresponding to a stress perturbation rate of −0.04 kPa/yr, much smaller than the tectonic loading rate. Because the fault zone straddles the coastline, the relative strengthening and weakening of different sections of the fault could possibly lead to a shift in the type of rupture on the CSZ.…”
Section: Eustatic Ocean Loading At the Cascadia Subduction Systemmentioning
confidence: 85%
“…Its seismicity is mostly located offshore: along the Mendocino Transform Fault (MTF), within the highly deformed Gorda plate, and along the Cascadia Subduction Zone (CSZ) (Figure 1). Paleoseismic evidence of great earthquakes along the CSZ [Atwater, 1987], including radiocarbon dating and several offshore turbidite episodes of deformation in the last 2000 years [Clarke and Carver, 1992], indicate that the CSZ is capable of multiple M8+ earthquakes, as large as M9 [Goldfinger et al, 2008;Satake et al, 1996;Heaton and Hartzell, 1987].…”
Section: Methodsmentioning
confidence: 99%
“…[6] In northern California, current realtime earthquake monitoring is performed sequentially by the U.S. Geological Survey at Menlo Park and the Berkeley Seismological Laboratory [Gee et al, 2003]. Because seismic stations are located onshore, poor azimuthal coverage of the seismic wave radiation patterns often leads to difficulties in detecting and locating events, and thus in determining their full source parameters.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Cascadia subduction zone is the over 1000km long boundary between the Juan de Fuca and North American plates. Geological evidence has shown that 13 significant earthquakes have occurred in the past 3000 years (Goldfinger et al 2008). The most notable of which, the M9.0 earthquake of 1700, produced a tsunami large enough to reach Japan (Atwater et al 2005).…”
Section: Generalmentioning
confidence: 99%